Method for recovering metal lithium in waste lithium battery positive electrode material
By using chromatographic separation technology of nitric acid solution and aminated polyacrylonitrile fibers in the lithium-ion battery positive electrode material, the problem of low metal lithium recovery efficiency in the lithium-ion battery positive electrode material is solved, and efficient metal lithium recovery and separation and purification of other metals is achieved.
Patent Information
- Application Number
- CN202411771934.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-04
AI Technical Summary
In the prior art, the recovery efficiency of metal lithium in the positive electrode material of lithium-ion batteries is low, resulting in waste of resources and environmental pollution.
The lithium-ion battery positive electrode material was dissolved using nitric acid solution, and the modified polyacrylonitrile fibers modified by diethylene triamine were used as filler to separate and recover lithium ions from the mixed solution through chromatographic separation technology.
The efficient recovery of lithium ions is achieved, with the recovery rate of lithium reaching 99.4%, while improving the recovery rate and purity of other metals.
Smart Images

Figure CN119640038A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of valuable metal recovery from waste batteries and relates to a method for recovering metallic lithium from positive electrode materials of waste lithium batteries. Background Art
[0002] Lithium-ion batteries have many advantages, including high operating voltage, high energy density, wide operating temperature range and long cycle life. The main types of lithium-ion battery positive electrode materials include lithium cobalt oxide, lithium manganese oxide, nickel cobalt manganese oxide ternary materials and nickel cobalt aluminum oxide ternary materials. Due to the rapid development of industries such as portable electronic devices, new energy electric vehicles and large-scale energy storage, the production and use of lithium-ion batteries has increased rapidly, and the demand for metal elements such as Co, Ni, Mn and Li has also increased sharply. Correspondingly, the number of retired and waste lithium-ion batteries will also increase rapidly. If these waste batteries are not properly disposed of, it will cause serious waste of resources. Compared with directly extracting these metal elements from raw materials, recycling lithium-ion batteries will ease resource pressure and reduce energy consumption and costs. In addition, the metal elements in waste lithium-ion batteries may also pollute soil and water sources. Therefore, the recycling of waste lithium-ion batteries has important economic and environmental value.
[0003] At present, the methods for recovering metal elements in the positive electrode materials of waste lithium batteries mainly include pyrometallurgy and hydrometallurgy. Pyrometallurgy is a method of directly using high-temperature treatment to extract metals or metal oxides from electrodes. The pyrometallurgical process is simple, but the purity of the recycled materials is low and the energy consumption is high. The electrolyte, binder and other organic matter in the battery will produce harmful gases due to high-temperature reactions, including CO, CO2, VOC, etc., and supporting facilities need to be installed for secondary waste gas treatment. At the same time, the high-temperature smelting process in direct pyrometallurgy will cause lithium loss. The hydrometallurgical method is to first disassemble the battery shell, crush and screen to obtain the electrode material, and the valuable metals in the electrode material are leached in acid or biological solution, and then separated to obtain the corresponding salts or oxides of each metal. The hydrometallurgical process mainly includes positive electrode pretreatment, valuable metal leaching, and valuable metal separation and recovery. Although the hydrometallurgical process can recover almost all metals from waste NCM batteries, the use of inorganic acids and alkalis as leaching agents will cause many environmental problems. Although organic acids are environmentally friendly, they are relatively expensive. And due to the high valence of the active cathode material in waste lithium batteries and the strong bonding of organic binders, some hydrometallurgical processes have the disadvantages of relatively long leaching times and low efficiency. During the leaching process, impurities such as aluminum and iron enter the acid solution together with lithium, nickel, cobalt and manganese, resulting in a long and cumbersome process of separating valuable metals from the leachate. Most importantly, lithium is also dispersed in these separation and refining stages, resulting in low lithium recovery rates. In recent years, adsorption chromatography separation technology has attracted extensive attention and research in the field of chromatographic separation. The working principle is to use the difference in distribution coefficients between the stationary phase adsorbent and the different components in the mobile phase, so that the retention capacity of different components in the adsorbent is different, thereby achieving efficient separation between substances. This method can effectively achieve the separation and purification of multiple components. When the solid and liquid phases move relative to each other, due to the different adsorption degrees of the stationary phase to each component in the solution, each component is distributed multiple times during the flow process. Even if there are slight differences in the distribution coefficients, a good distribution effect can be achieved, thereby achieving efficient separation of multiple components. The Chinese patent application with publication number CN116262946A discloses a method for separating and extracting valuable metals from the acidic leachate of waste battery ternary materials using a chromatographic separation system, but the method uses a series countercurrent chromatographic separation system and a bipolar membrane electrodialysis system to separate and recover four metal ions through a multi-stage separation system, and the separation process is relatively cumbersome. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for recovering metallic lithium in the positive electrode material of waste lithium batteries, thereby solving the technical problem of low lithium recovery efficiency in the prior art.
[0005] The present invention is achieved through the following technical solutions: A method for recovering metallic lithium from anode materials of waste lithium batteries comprises the following steps: S1: dissolving the lithium-ion battery positive electrode material to be recycled in a nitric acid solution to obtain a raw solution to be recycled; S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within six column volumes; S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
[0006] Preferably, the column volume of the packed chromatographic column is 10 to 20 cm 3 .
[0007] Preferably, the filling amount of the filler in the packed chromatographic column is 8 to 15 cm 3 .
[0008] Preferably, before the raw solution to be recovered is injected into the packed chromatographic column, the pH value of the raw solution to be recovered is adjusted to 2-6.
[0009] Preferably, before the recovered stock solution is injected into the packed chromatographic column, the concentration of the recovered stock solution is adjusted to 0.1-20 mmol / L.
[0010] Preferably, the flow rate of the recovered stock solution in the packed chromatographic column is 0.05-0.60 mL / min.
[0011] Preferably, in step S2, the effluent within the first three column volumes is collected.
[0012] Preferably, in step S3, the packed chromatographic column is replaced with a packed chromatographic column that has not been treated with adsorption or a packed chromatographic column that has been treated with elution with an eluent.
[0013] Preferably, the eluent is nitric acid with a concentration of 0.01-0.2 mol / L.
[0014] Preferably, during elution, the eluent used is 10 to 12 column volumes.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for recovering metallic lithium in positive electrode materials of waste lithium batteries. The method firstly dissolves the positive electrode materials by nitric acid solution to ensure the effective release of metallic lithium, then uses aminated polyacrylonitrile fiber as filler, introduces amino functional groups into the polyacrylonitrile fiber by amination modification with diethylenetriamine, and the modified fiber has selective adsorption of metal ions. These amino functional groups have strong complexing ability for transition metal ions, and effectively realize the recovery of lithium ions in mixed metal solutions. The aminated polyacrylonitrile fiber generates OH in water. - Ions can exchange with various anions to adsorb anions, and can form coordination bonds with metal ions with N as a coordinating atom to achieve effective adsorption of metal cations. The present invention uses a primary chromatography separation system to separate Li from a mixed solution, and the recovery rate of Li exceeds 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0017] Figure 1 It is a schematic diagram of the structure of the separation device in the present invention; Figure 2 This is a schematic diagram of the principle of separating metal ions using aminated fibers in the present invention; Figure 3 The adsorption curve (a) and elution curve (b) of metal ions in the positive electrode material of a ternary lithium-ion battery in Example 1 of the present invention; Figure 4The adsorption curve (a) and elution curve (b) of metal ions in the Co-Li system in Example 2 of the present invention; Figure 5 The adsorption curve (a) and elution curve (b) of metal ions in the Mn-Li system in Example 3 of the present invention; Figure 6 This is a diagram showing the effect of different mixed solution acidity values on the adsorption of mixed metal ions by fibers in the present invention; Figure 7 This is a diagram showing the separation effect of metal ions at an injection concentration of 10 mmol / L in the present invention; Figure 8 The fiber-filled adsorption column of the present invention has a filling length of full column, and the fiber has a Li + 、Ni 2+ 、Co 2+ , Mn 2+ The adsorption curve of Fig. 9 In the present invention, when the peristaltic pump power is 2.0 rpm, the fiber Li + 、Ni 2+ 、Co 2+ , Mn 2+ The adsorption curve of Fig.10 When the elution acid concentration is 0.2 mol / L, Li + 、Ni 2+ 、Co 2+ , Mn 2+ The elution curve of Fig.11 For the (a) Li on the fiber after adsorption in Example 1 + (b)Ni 2+ 、(c)Co 2+ (d)Mn 2+ XPS spectrum of Fig.12 In Example 1, the (e)Li + 、(f)Ni 2+ , (g) Co 2+ 、(h)Mn 2+ XPS spectrum of Fig.13 The electron micrographs (a) of the fibers before metal adsorption in Example 1, (b) of the fibers after metal adsorption, and (c) of the fibers after elution.
[0018] Among them, 1. beaker, 2. peristaltic pump, 3. sampling hose, 4. fiber adsorption column, 5. automatic collector. DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0020] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0021] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0022] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0023] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0024] The present invention provides a method for recovering metallic lithium from anode materials of waste lithium batteries, comprising the following steps: S1: dissolving the lithium-ion battery positive electrode material to be recycled in a nitric acid solution to obtain a raw solution to be recycled; Wherein, the lithium-ion battery includes a ternary lithium-ion battery, a lithium cobalt oxide battery or a lithium manganese oxide battery; the concentration of the nitric acid solution here is 0.2 mol / L.
[0025] S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within six column volumes; Among them, the column volume of the packed column is 10~20 cm 3 The filling volume of the packed column is 8~15 cm 3 .
[0026] Preferably, before the raw solution to be recovered is injected into the packed chromatographic column, the pH value of the raw solution to be recovered is adjusted to 2-6.
[0027] Before injecting the recovered stock solution into the packed chromatographic column, the concentration of the recovered stock solution is adjusted to 0.1-20 mmol / L.
[0028] The flow rate of the recovered stock solution in the packed chromatographic column is 0.05-0.60 mL / min.
[0029] In a more preferred embodiment, the effluent within the first three column volumes is collected.
[0030] The preparation process of the polyacrylonitrile fiber modified by diethylenetriamine amination in the present invention is as follows: A certain volume of diethylenetriamine is put into a high-pressure reactor, and a certain mass of polyacrylonitrile fiber is placed in the system and stirred evenly, so that the ratio of diethylenetriamine to polyacrylonitrile fiber is 5mL:1g, and then sodium carbonate solution is added, stirred evenly, and the reaction system is reacted at 115°C for 5 hours to obtain the polyacrylonitrile fiber modified by diethylenetriamine. Among them, the ratio of polyacrylonitrile fiber to sodium carbonate solution is 1g:1mL, and the concentration of sodium carbonate solution is 0.01g / mL.
[0031] S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
[0032] The packed chromatographic column is replaced with a packed chromatographic column that has not been treated with adsorption or a packed chromatographic column that has been treated with elution with an eluent.
[0033] The eluent is nitric acid with a concentration of 0.01-0.2 mol / L.
[0034] During elution, the eluent used is 10 to 12 column volumes.
[0035] In this study, aminated fibers were used as adsorption carriers and the constructed separation device was used to separate the waste NCM battery cathode material Li by adsorption chromatography separation technology. + Recycling. Figure 1 As shown, the separation device consists of a beaker 1, a peristaltic pump 2, a sampling hose 3, a fiber adsorption column 4 and an automatic collector 5. The raw solution to be recovered is pumped into the fiber adsorption column 4 by the peristaltic pump 2. During the adsorption process, due to the difference in the distribution coefficient between the adsorption fiber and the metal ions in the mixed solution, the retention capacity of each metal ion in the adsorbent is different, so that the metal ions are distributed multiple times during the flow process, thereby achieving efficient separation between the metal ions.
[0036] like Figure 2As shown, the present invention adopts chromatographic separation technology, using polyacrylonitrile fiber modified by diethylenetriamine as an adsorption carrier, to separate and recover the valuable metals Li, Ni, Co, and Mn in the positive electrode materials of waste ternary lithium batteries, and to separate and recover Co and Li in the positive electrode materials of lithium cobalt oxide in the binary system, and Mn and Li in the positive electrode materials of lithium manganate. In the multi-element system column adsorption-elution process, under the optimal adsorption and elution conditions, the recovery rate of Li is 99.4%, the recovery rate of Ni is 80.2%, the recovery rate of Co is 89.8%, and the recovery rate of Mn is 71.4%. The purity of Ni, Co, and Mn in the effluent of the 5th BV is 65.5%, 22%, and 12.5%, respectively. In the binary lithium cobalt oxide system, under the optimal adsorption and elution conditions, the recovery rate of Li is 96.1%, and the recovery rate of Co is 99.6%. In the binary lithium manganate system, under the optimal adsorption and elution conditions, the recovery rate of Li is 96.4%, and the recovery rate of Mn is 99.3%.
[0037] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0038] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0039] Example 1 In this example, column adsorption separation technology is used to separate four metals, Li, Ni, Co, and Mn, from the mixed solution of the positive electrode material of the ternary lithium-ion battery. Use an electronic balance to accurately weigh 10.0 g of aminated polyacrylonitrile fiber, and soak the fiber in deionized water at 25 °C for 12 h to completely soak the fiber. Insert the soaked adsorption fiber into the adsorption column, and fill the adsorption column with the fiber to the full length. During the filling process, use a glass rod to compress the fiber to minimize the gap between the fibers. The concentration of the ternary mixed solution is 10 mmol / L, and the peristaltic pump power is adjusted to 1.0 rpm (the flow rate of the injection solution is 0.29 mL / min). After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution, put it into a 10 mL centrifuge tube, and dilute it 50 times. After the adsorption is completed, the injection solution in the adsorption column and the inlet and outlet pipes is completely discharged, and then the injection solution is replaced with 0.2 mol / L nitric acid to elute the metals adsorbed on the fiber. After the reaction, use a 0.2 mL pipette to take 0.2 mL of the solution into a 10 mL centrifuge tube and dilute it 50 times. Use ICP-OES to measure the concentration of metal ions in the solution.
[0040] The results showed that the separation of the four metal ions was better under the optimal adsorption-elution conditions of mixed solution pH 2, injection solution concentration of 10 mmol / L, adsorption fiber filling to full column, peristaltic pump power of 1.0 rpm, and eluent nitric acid concentration of 0.2 mol / L. Figure 3 As shown in Figure (a), during the adsorption process, Li is separated from Ni, Co, and Mn at the 2nd BV, and there are 5 BV separation intervals, and the recovery rate of Li is 99.4%. Ni, Co, and Mn also begin to separate at 12 BV, and at 32 BV, the entire adsorption process reaches adsorption equilibrium. Therefore, Li can be separated from Ni, Co, and Mn through the adsorption process. In addition, Figure 3 As shown in Figure (b), during the elution process, Ni has an ideal separation effect at 1 BV, and Co and Mn have an ideal separation effect at 5 BV. At the same time, they can be completely eluted from the fiber in a smaller column volume of 10 BV. In the first 5 BV, the recovery rate of Ni is 80.2%, the recovery rate of Co is 89.8%, and the recovery rate of Mn is 71.4%. The purity of Ni, Co, and Mn in the effluent of the 5th BV is 65.5%, 22%, and 12.5%, respectively.
[0041] Example 2 In this example, the column adsorption separation technology is used to separate the two metals Co and Li in the mixed solution of the binary system lithium cobalt oxide positive electrode material. Use an electronic balance to accurately weigh 10.0 g of aminated polyacrylonitrile fiber, and soak the fiber in deionized water at 25 °C for 12 h to completely soak the fiber. Insert the soaked adsorption fiber into the adsorption column, and the fiber fills the adsorption column to the full length of the column. During the filling process, the glass rod is continuously used to compress the fiber to minimize the gap between the fibers. The concentration of the lithium cobalt oxide positive electrode material mixture is 10 mmol / L, and the peristaltic pump power is adjusted to 1.0 rpm. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution, put it into a 10 mL centrifuge tube, and dilute it 50 times. After the adsorption is completed, the injection solution in the adsorption column and the inlet and outlet pipes is completely discharged, and then the injection solution is replaced with 0.2 mol / L nitric acid to elute the metal adsorbed on the fiber. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution into a 10 mL centrifuge tube and dilute it 50 times. ICP-OES was used to measure the concentration of metal ions in the solution.
[0042] The results are as follows Figure 4 As shown, according to Figure 4 As can be seen in Figure (a), the fiber basically does not adsorb Li. The concentration of Li in the effluent at the 3rd BV is basically the same as that in the feed solution, and C / C0 is 0.99. The two metals Co and Li begin to separate at the 2nd BV, and Co begins to appear in the effluent after the 16th BV. The separation range of Co-Li during the adsorption process reaches 15 BV. The entire adsorption process reaches adsorption equilibrium at about 45 BV, and the recovery rate of Li is 99.1%. According to Figure 4 As can be seen in Figure (b), at the 6th BV, the separation effect of the two metals Co-Li is the best. At this time, the separation factor is the largest in the entire elution process. 2+ The concentration of 2-nitrogen-2-thiocyanate (2-nitrogen-2-thiocyanate) was the highest, and the entire elution process was completed within 15 BV, the column volume consumed was small, and the recovery rate of Co was 99.6%. In summary, the fiber showed good performance in the adsorption separation of Co-Li, a lithium cobalt oxide cathode material, and the column adsorption separation technology can achieve efficient separation of Co-Li.
[0043] Example 3 In this example, column adsorption separation technology is used to separate the two metals Mn and Li in the mixed solution of the binary system lithium manganate positive electrode material. Use an electronic balance to accurately weigh 10.0 g of aminated polyacrylonitrile fiber, and soak the fiber in deionized water at 25 °C for 12 h to completely soak the fiber. The soaked adsorption fiber is inserted into the adsorption column, and the fiber fills the adsorption column length to the full column. During the filling process, the fiber is continuously compressed with a glass rod to minimize the gap between the fibers. The concentration of the lithium manganate positive electrode material mixture is 10 mmol / L, the peristaltic pump power is adjusted to 1.0 rpm, and the sample solution is collected with an automatic collector. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution, put it into a 10 mL centrifuge tube, and dilute it 50 times. After the adsorption is completed, all the sample solutions in the adsorption column and the inlet and outlet pipes are discharged, and then the sample solution is replaced with 0.2 mol / L nitric acid to elute the metals adsorbed on the fiber. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution into a 10 mL centrifuge tube and dilute it 50 times. Use ICP-OES to determine the concentration of metal ions in the solution. The test results are shown in Figure 5 As can be seen from the figure, the fiber basically does not adsorb Li. The concentration of Li in the effluent at the 4th BV is basically the same as that in the feed solution, and C / C0 is greater than 1.0. The two metals Mn and Li begin to separate at the 2nd BV, and Mn begins to appear in the effluent after the 15th BV. The separation range of Mn and Li during the adsorption process reaches 13 BV, and the entire adsorption process reaches adsorption equilibrium at about 44 BV. According to Figure 5 It can be found in Figure (b) that the separation effect of the two metals Mn-Li is better at 8-13 BV, and the entire elution process ends at about 34 BV. The column volume consumed is large, but the effect of separating the two metals can be achieved. After column separation, the recovery rate of Li is 99.3%, and the recovery rate of Mn is 99.3%. In summary, the fiber in the present invention shows good performance in the adsorption and separation of Mn-Li in lithium manganate positive electrode materials, and the column adsorption separation technology can achieve the separation of Mn-Li.
[0044] In order to further verify the effect of the acidity of the recovered raw liquid on the separation efficiency, the following examples were carried out.
[0045] Example 4 Use an electronic balance to accurately weigh six portions of 0.2 g fiber and place them in a dry place for later use. Use a 10 mL pipette to measure 30 mL of waste NCM battery positive electrode material (Li + 、Ni 2+ 、Co 2+ , Mn 2+The molar ratio is 1:1:1:1) and the simulated mixed solution is added to the conical flask, and the pH value of the mixed solution is adjusted to 1 with 0.1 mol / L HNO3 and 0.1 mol / L NaOH solution. The weighed adsorption fiber is placed in the conical flask, the conical flask is sealed and labeled, and the conical flask is placed in a constant temperature water bath shaker, and shaken for 24 hours at 25°C and a shaking rate of 160 rpm. After the reaction, the supernatant is filtered out with a 0.45 μm filter membrane, and 1 mL of the solution is taken with a 10 mL pipette and placed in a 10 mL centrifuge tube. After diluting several times, the Li in the solution is determined using ICP-OES. + 、Ni 2 + 、Co 2+ , Mn 2+ concentration and draw a pH-C / C0 graph.
[0046] Example 4 First, use an electronic balance to accurately weigh 0.10-1.0 g of fiber and place it in a dry place for later use. Use a 10 mL pipette to measure 10-30 mL of the simulated mixed solution of waste NCM battery positive electrode materials (Li + 、Ni 2+ 、Co 2+ , Mn 2+ The molar ratio of 1:1:1:1) was placed in a 50 mL glass conical flask and the pH was adjusted to 1-6. The fiber was placed in the conical flask, sealed, and placed in a constant temperature oscillating box for 24 hours at 25 °C and an oscillation rate of 160 rpm. After the reaction was completed, the solution was filtered out with a 0.45 μm filter membrane, and 0.1-1 mL was taken with a 1 mL pipette and placed in a 10 mL centrifuge tube. After diluting several times, the Li in the solution was determined by ICP-OES. + 、Ni 2+ 、Co 2+ , Mn 2+ The concentration of the fiber was calculated according to formula (1) to obtain the adsorption selectivity coefficient K of each metal. d .
[0047] Distribution coefficient (adsorption selectivity coefficient) K d It refers to the concentration ratio of the solute adsorbed in the solid adsorbent to the solute remaining in the solvent in the adsorption equilibrium state, reflecting the distribution of each component solute between the adsorbent and the solution phase and the migration ability of each component solute in the two phases. The larger the distribution coefficient of the ion on the adsorbent, the easier it is to be adsorbed by the adsorbent.
[0048] Partition coefficient K d The calculation formula is as follows: (1) Where: is the initial concentration of metal ions (mg / L); is the equilibrium concentration of metal ions (mg / L); V is the volume of the solution (L); is the mass of the fiber (g).
[0049] It can be seen from Example 10 that the adsorption selectivity coefficient (partition coefficient) K of the adsorption fiber of the present invention for each metal is d As shown in Table 1. By comparison, it can be obtained that the order of adsorption selection of the four metals in the mixed solution of the positive electrode material of the waste ternary lithium battery by the fiber is: Ni 2+ >Co 2+ >Mn 2+ >Li + , indicating that during the adsorption process, Ni 2+ is the first to be adsorbed on the fiber, Li + is the last one to be adsorbed. + with Ni 2+ 、Co 2+ , Mn 2+ The distribution coefficients on the fibers vary greatly, so that Li + with Ni 2+ 、Co 2+ , Mn 2+ Separation.
[0050] Table 1 Distribution coefficients of four metal ions on the aminated fibers in this invention
[0051] At the same time, the separation factor SF was calculated by formula (2). The initial separation factors of the four metal ions on the fiber are shown in Table 2. When the separation factor SF is greater than 1, it means that the two can be effectively separated.
[0052] Table 2 Initial separation factors of four metal ions on fibers
[0053] The calculation formula of separation factor SF is as follows: (2) Where: is the distribution coefficient of metal ion A; is the distribution coefficient of metal ion B.
[0054] Example 6 The difference from Example 3 is that the pH value of the mixed solution is adjusted to 2 using 0.1 mol / L HNO3 and 0.1 mol / L NaOH solutions.
[0055] Example 7 The difference from Example 3 is that the pH value of the mixed solution is adjusted to 3 using 0.1 mol / L HNO3 and 0.1 mol / L NaOH solutions.
[0056] Example 8 The difference from Example 3 is that the pH value of the mixed solution is adjusted to 4 using 0.1 mol / L HNO3 and 0.1 mol / L NaOH solutions.
[0057] Example 9 The difference from Example 3 is that the pH value of the mixed solution is adjusted to 5 using 0.1 mol / L HNO3 and 0.1 mol / L NaOH solutions.
[0058] Example 10 The difference from Example 3 is that the pH value of the mixed solution is adjusted to 6 using 0.1 mol / L HNO3 and 0.1 mol / L NaOH solutions.
[0059] The pH values in Examples 5 to 10 were compared with the C / C0 of the four metal ions in the system after adsorption treatment. The results are as follows: Figure 6 As shown by Figure 6 It can be seen that the separation effect of the four metal ions is poor when the pH value is low or high, especially the separation effect between the transition metals nickel and manganese is poor. This may be due to the fact that Ni, Co, and Mn are transition metals with similar properties, resulting in similar adsorption capacity of the fiber for Ni, Co, and Mn. When the pH of the mixed solution is 2 and 4, Li + 、Ni 2+ 、Co 2+ , Mn 2+ The separation effect between the three transition metal elements of nickel, cobalt and manganese is very good, but when the pH is too high, Ni 2+ 、Co 2+ , Mn 2+ Some precipitation may occur, which is not conducive to adsorption separation, so the pH of the mixed solution was adjusted to 2 in the subsequent column chromatography separation study. It is worth noting that when the pH value of the mixed solution is in the range of 2 to 6, effective separation and recovery of lithium ions can be achieved.
[0060] Embodiment 11 This example investigates the effect of different inlet solution concentrations on the adsorption of Li + 、Ni 2+ 、Co 2+, Mn 2+ The effect of four metal ion separation. First, fill the fully wetted adsorption fiber into the adsorption column, dilute the concentration of the simulated mixed solution of the waste NCM battery positive electrode material by several times, use the peristaltic pump to inject the sample, fix the peristaltic pump power, and use the automatic collector to collect the flow solution. After the reaction is completed, use a 1 or 0.2 mL pipette to take a certain volume of solution and put it into a 10 mL centrifuge tube. After diluting it a certain number of times, use ICP-OES to determine the Li + 、Ni 2+ 、Co 2+ , Mn 2+ The BV-C / C0 graph was drawn based on the concentration of the sample solution. The effects of different sample solution concentrations on the adsorption and separation of four metal ions in the fiber adsorption mixed solution were analyzed to determine the optimal sample solution concentration. The sample concentration varied from 0.1 to 20 mmol / L, and the most preferred sample concentration was 10 mmol / L. The separation effect of metal ions at this sample concentration was shown in Table 1. Figure 7 As shown in the figure, when the injection concentration is 10 mmol / L, the two metals Ni and Co with similar properties can not only start to separate at a minimum of 12 BV, but also reach adsorption equilibrium at 30 BV during the entire adsorption process. At the same time, through the adsorption curve of the injection concentration of , it can be found that Li has liquid produced at the 2nd BV, and has reached adsorption equilibrium at the 3rd BV, and C / C0 is close to 1.0. This shows that Li is less competitive than Ni, Co, and Mn, and the fiber hardly adsorbs Li.
[0061] Example 12 In order to study the effect of fiber-filled adsorption column length on adsorption separation, the following examples were conducted. The experiment explored the effect of different fiber-filled column lengths on fiber adsorption of Li + 、Ni 2+ 、Co 2+ , Mn 2+ The influence of four metal ion separation effects. The fully soaked adsorption fiber is inserted into the adsorption column. The length of the fiber adsorption column is 1 / 5 of the column length ~ full column. During the filling process, a glass rod is continuously used to compress the fiber to minimize the gap between the fibers. The concentration of the simulated mixed solution of the discarded NCM battery positive electrode material and the power of the peristaltic pump are fixed, and the sample solution is collected with an automatic collector. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution, put it into a 10 mL centrifuge tube, dilute it 50 times, and use ICP-OES to determine the Li in the solution. + 、Ni 2+ 、Co 2+ , Mn 2+The BV-C / C0 graph was drawn to analyze the effect of different fiber-filled adsorption column lengths on the adsorption and separation of four metal ions in the fiber adsorption mixed solution, so as to determine the optimal fiber-filled column length and concentration. The analysis results show that the best filling is full column filling. In the case of full column filling, the analysis effects of the four metal ions are shown in Figure 8 As can be seen from the figure, when the fiber filling column length is the full column length, Li and the other three metals have a better separation effect. The effluent from the 2nd to the 6th column volume is all Li. This shows that the more volume the aminated polyacrylonitrile fiber fills in the adsorption column, the better the fiber's adsorption and separation effect on Li and Ni, Co, and Mn will be.
[0062] Example 13 Under the condition that the concentration of the sample solution and the length of the fiber-filled adsorption column remain unchanged, this example investigates the effect of different peristaltic pump powers (sample flow rates) on the fiber adsorption of Li + 、Ni 2+ 、Co 2+ , Mn 2+ The effect of four metal ion separation. Specifically: first fill the fully wetted adsorption fiber into the adsorption column (the weight of the fiber and the filling method are the same as above), fix the concentration of the simulated mixed solution of the waste NCM battery positive electrode material, use a peristaltic pump to inject, thereby changing the flow rate of the injection solution, and use an automatic collector to collect the sample solution. After the reaction is completed, use a 0.2 mL pipette to take 0.2 mL of the solution into a 10 mL centrifuge tube, dilute it 50 times, and use ICP-OES to determine the Li + 、Ni 2+ 、Co 2+ , Mn 2+ The concentration of the fiber adsorption was analyzed by plotting the BV-C / C0 graph to analyze the effect of different peristaltic pump powers on the adsorption and separation of four metal ions in the mixed solution, so as to determine the optimal peristaltic pump power. In the experiment, the peristaltic pump power was set to 1.0. The test results are shown in Fig. 9 ,Depend on Fig. 9 As shown in the figure, when the peristaltic pump power is 1.0 rpm, the flow rate of the injection solution is moderate, and the separation effect between Li and the three metals Ni, Co, and Mn is good, with a separation interval of 5 BV, and the entire adsorption process reaches adsorption equilibrium at a column volume of about 32 BV. Ni and Co began to separate at the 12th BV, and the C / C0 calculated by the Li content in the effluent at the 2nd BV had reached 0.97, which is approximately equivalent to the Li concentration in the injection solution, indicating that there is almost no Li adsorbed on the fiber at this time, and Li has been replaced by the other three metals.
[0063] Through the analysis of Examples 4 to 13, during the adsorption process, Li is separated from Ni, Co, and Mn at the second BV, and there are 5 BV separation intervals. The recovery rate of Li calculated by formula (3) is 99.4%.
[0064] The recovery rate R is calculated as follows: (3) Where: is the mass of the target component in the solution after separation; is the mass of the target component in the solution before separation.
[0065] Embodiment 14 In order to study the effect of eluent concentration on elution effect, the following examples were performed: After the fiber reaches adsorption saturation, the injection solution in the adsorption column and the inlet and outlet pipes is completely discharged, and then the injection solution is replaced with nitric acid to react with the Li adsorbed on the fiber. + 、Ni 2+ 、Co 2+ , Mn 2+ Elution was performed to explore the effect of different nitric acid concentrations on Li + 、Ni 2+ 、Co 2+ , Mn 2+ The effect of elution. Set the concentration of elution acid to 0.01~0.2 mol / L, adjust the peristaltic pump power to 1.0 rpm, and collect the sample solution with an automatic collector. After elution is completed (the fiber will turn light yellow), use a 0.2 mL pipette to take 0.1~0.2 mL of the solution into a 10 mL centrifuge tube, dilute it 50~100 times, and use ICP-OES to determine the Li in the solution. + 、Ni 2+ 、Co 2+ , Mn 2+ The BV-C / C0 graph was drawn to analyze the effect of different nitric acid concentrations on the elution of the four metal ions adsorbed on the fiber and determine the optimal elution acid concentration. Fig.10 , Fig.10The concentration of nitric acid in the eluent is 0.2 mol / L. When the concentration of nitric acid is 0.2 mol / L, the separation effect between the four metal ions is the most ideal. Not only can the metals on the fiber be completely eluted and separated in a smaller column volume of 10 BV, but the separation effect between the transition metals nickel, cobalt and manganese is also very significant. From the 1st BV to the 5th BV, Ni, Co and Mn have good separation effects, especially in the 3rd and 4th BV, the C / C0 of Ni content in the effluent reaches about 3.0, indicating that the concentration of Ni in the effluent is very high. At the same time, Ni, Co and Mn can be completely eluted from the fiber in a smaller column volume of 10 BV. According to formulas (3) and (4), the recovery rates of Ni, Co and Mn in the first 5 BV are 80.2%, 89.8% and 71.4%, respectively. The purities of Ni, Co and Mn in the effluent of the 5th BV are 65.5%, 22% and 12.5%, respectively.
[0066] Among them, the purity P calculation formula is as follows: (4) Where: is the mass of metal ion A in the solution after separation; is the mass of metal ion B in the solution after separation.
[0067] Embodiment 15 In this example, XPS characterization analysis was performed on the fibers after adsorption and elution in Example 1. The XPS spectrum of the fibers after adsorption is shown in FIG. Fig.11 After elution, the XPS of the fiber is shown Fig.12 . As can be seen from the figure, after adsorption, the four metals Li, Ni, Co, and Mn all have obvious peaks, indicating that the fiber adsorbs the four metal ions. The Li peak intensity is weaker, the Ni peak intensity is stronger, and the peak intensities of the two metals Co and Mn are second, indicating that the amount of Li adsorbed by the fiber is the least, and the concentration of Li on the fiber surface is lower; the amount of Ni adsorbed is the largest, and the concentration of Ni on the fiber surface is the highest, which is consistent with the conclusion obtained from the adsorption process. After elution, the four metals Li, Ni, Co, and Mn have no peaks, and the metal ions adsorbed on the surface fiber have been completely eluted. Therefore, it is feasible to use fiber as an adsorption material to separate the four metals from the ternary nickel-cobalt-manganese mixed solution by adsorption-elution.
[0068] Example 16 This example tests the surface morphology of the fiber in Example 1 before and after metal adsorption and after acid elution. The test results are shown in Fig.13As can be seen from the figure, the fiber surface is relatively smooth before the adsorption of metal ions. A small number of small grooves and scratches may be caused by the modification process. After the adsorption of metal ions, the surface morphology of the fiber has changed significantly. After adsorption, the fiber surface becomes rough and has a lot of protrusions. This is caused by the adsorption of metal ions by the fiber, indicating that the fiber has a good adsorption effect on metals. After acid elution, the metal adsorbed on the fiber is completely eluted. Compared with the original state, the fiber surface becomes smooth and the adsorbed metal ions are eluted.
[0069] The present invention mainly adopts chromatographic separation technology, uses polyacrylonitrile fiber modified by diethylenetriamine amination as an adsorption carrier, separates and recovers the valuable metal LiNiCoMn in the positive electrode material of waste ternary lithium battery, and separates and recovers Co-Li in the positive electrode material of binary system lithium cobalt oxide, and Mn-Li in the positive electrode material of lithium manganate. In the multi-element system column adsorption-elution process, under the optimal adsorption and elution conditions, the recovery rate of Li is 99.4%, the recovery rate of Ni is 80.2%, the recovery rate of Co is 89.8%, and the recovery rate of Mn is 71.4%. The purity of Ni, Co, and Mn in the 5th BV effluent is 65.5%, 22%, and 12.5%, respectively. In the binary lithium cobalt oxide system, under the optimal adsorption and elution conditions, the recovery rate of Li is 96.1%, and the recovery rate of Co is 99.6%. In the binary lithium manganate system, under the optimal adsorption and elution conditions, the recovery rate of Li is 96.4%, and the recovery rate of Mn is 99.3%.
[0070] Embodiment 17 A method for recovering metallic lithium from anode materials of waste lithium batteries comprises the following steps: S1: dissolving the positive electrode material of the ternary lithium-ion battery to be recycled in a nitric acid solution to obtain a raw solution to be recycled; S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within six column volumes; The column volume of the packed column is 10 cm 3 The filling volume of the packed column is 8 cm 3 .
[0071] Preferably, before the raw solution to be recovered is injected into the packed chromatographic column, the pH value of the raw solution to be recovered is adjusted to 2, and the concentration of the raw solution to be recovered is adjusted to 0.1 mmol / L.
[0072] The flow rate of the recovered raw solution in the packed chromatographic column is 0.05 mL / min.
[0073] S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
[0074] The packed chromatographic column is replaced with a packed chromatographic column that has been eluted with an eluent. During elution, the eluent is nitric acid with a concentration of 0.01 mol / L. The eluent used is 10 column volumes.
[0075] Embodiment 18 A method for recovering metallic lithium from anode materials of waste lithium batteries comprises the following steps: S1: dissolving the lithium cobalt oxide battery positive electrode material to be recycled in a nitric acid solution to obtain a recycled stock solution; S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within three column volumes; The column volume of the packed column is 20 cm 3 The filling volume of the packed column is 15 cm 3 .
[0076] Preferably, before the raw solution to be recovered is injected into the packed chromatographic column, the pH value of the raw solution to be recovered is adjusted to 6, and the concentration of the raw solution to be recovered is adjusted to 20 mmol / L.
[0077] The flow rate of the recovered raw liquid in the packed chromatographic column is 0.60 mL / min.
[0078] S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
[0079] The packed chromatographic column is replaced with a packed chromatographic column that has been eluted with an eluent. During elution, the eluent is nitric acid with a concentration of 0.2 mol / L. The eluent used is 12 column volumes.
[0080] Embodiment 19 A method for recovering metallic lithium from anode materials of waste lithium batteries comprises the following steps: S1: dissolving the positive electrode material of the lithium manganese oxide battery to be recycled in a nitric acid solution to obtain a raw solution to be recycled; S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within five column volumes; The column volume of the packed column is 15 cm 3 The filling volume of the packed column is 15 cm 3 .
[0081] Preferably, before the recovered stock solution is injected into the packed chromatographic column, the pH value of the recovered stock solution is adjusted to 4, the concentration of the recovered stock solution is adjusted to 10 mmol / L, and the flow rate of the recovered stock solution in the packed chromatographic column is 0.10 mL / min.
[0082] S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
[0083] The packed chromatographic column is replaced with a packed chromatographic column that has been eluted with an eluent. During elution, the eluent is nitric acid with a concentration of 0.1 mol / L. The eluent used is 11 column volumes.
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for recovering metallic lithium from positive electrode materials of waste lithium batteries, characterized in that: The following steps are involved: S1: dissolving the lithium-ion battery positive electrode material to be recycled in a nitric acid solution to obtain a raw solution to be recycled; S2: injecting the raw solution to be recovered into a packed chromatographic column, wherein the packed material is polyacrylonitrile fiber modified by diethylenetriamine amination, and collecting the effluent within six column volumes; S3: Replace the packed chromatographic column and continue to repeat step S2 until all samples to be recovered have been processed, thereby completing the recovery of metallic lithium in the waste lithium battery material.
2. The method for recovering metallic lithium from positive electrode materials of waste lithium batteries according to claim 1, characterized in that: The column volume of the packed chromatographic column is 10-20 cm 3 .
3. The method for recovering metallic lithium from positive electrode materials of waste lithium batteries according to claim 1, characterized in that: The filling amount of the filler in the packed chromatographic column is 8-15 cm 3 .
4. The method for recovering metallic lithium from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: Before injecting the recovered stock solution into the packed chromatographic column, the pH value of the recovered stock solution is adjusted to 2-6.
5. The method for recovering metallic lithium from positive electrode materials of waste lithium batteries according to claim 1, characterized in that: Before injecting the recovered stock solution into the packed chromatographic column, the concentration of the recovered stock solution is adjusted to 0.1-20 mmol / L.
6. The method for recovering metallic lithium from positive electrode materials of waste lithium batteries according to claim 1, characterized in that: The flow rate of the recovered stock solution in the packed chromatographic column is 0.05-0.60 mL / min.
7. The method for recovering metallic lithium from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: In step S2, the effluent within the first three column volumes is collected.
8. The method for recovering metallic lithium from the positive electrode material of waste lithium batteries according to claim 1, characterized in that: In step S3, the packed chromatographic column is replaced with a packed chromatographic column that has not been treated with adsorption or a packed chromatographic column that has been treated with elution with an eluent.
9. The method for recovering metallic lithium from the positive electrode material of waste lithium batteries according to claim 8, characterized in that: The eluent is nitric acid with a concentration of 0.01-0.2 mol / L.
10. The method for recovering metallic lithium from positive electrode materials of waste lithium batteries according to claim 8, characterized in that: During elution, the eluent used is 10 to 12 column volumes.
Citation Information
Patent Citations
Method for separating and extracting valuable metal from waste battery ternary material acid leaching solution by utilizing chromatographic separation system
CN116262946A
Ethylene polymer fine particles, functional group-containing ethylene polymer fine particles, and catalyst carrier for production thereof
CN101061144A
Precious metal extraction method for waste lithium battery in airport service vehicle
CN112143897A
PEO-based solid electrolyte as well as preparation method and application thereof
CN113270639A
Rapid detection method for impurity ion content and main content of solid lithium salt
CN115308353A